Is there responsible gendered governance of forest tenure? Getting a clear picture. Training Handbook - Jhaveri, N.J. (Center for International Forestry Research, 2021)
The content of the handbook and its handouts are illustrative and can be tailored to different training requirements. For example, if the course is used for government staff or members of a non-governmental organization, the content and exercises can be adjusted to suit the knowledge background and interests of participants.